2017
DOI: 10.1021/acsphotonics.7b00127
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Optical Properties of Plasmonic Titanium Nitride Thin Films

Abstract: Due to their exceptional plasmonic properties, noble metals such as gold and silver have been the materials of choice for the demonstration of various plasmonic and nanophotonic phenomena. However, noble metals' softness, lack of tailorability and low melting point along with challenges in thin film fabrication and device integration have prevented the realization of real-life plasmonic devices. In the recent years, titanium nitride (TiN) has emerged as a promising plasmonic material with good metallic and ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
142
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(153 citation statements)
references
References 43 publications
10
142
0
1
Order By: Relevance
“…By changing its stoichiometry and film thickness, TiN exhibits tunable electrical conductivity and optical absorption across many wavelengths . In detail, the dielectric properties of TiN 1‐x can be controlled by tuning the reactive nitrogen ratio and deposited temperatures . It is found that TiN 1‐x exhibits plasmonic phenomena in visible and near‐infrared region when x ≅ 0 .…”
Section: Introductionmentioning
confidence: 99%
“…By changing its stoichiometry and film thickness, TiN exhibits tunable electrical conductivity and optical absorption across many wavelengths . In detail, the dielectric properties of TiN 1‐x can be controlled by tuning the reactive nitrogen ratio and deposited temperatures . It is found that TiN 1‐x exhibits plasmonic phenomena in visible and near‐infrared region when x ≅ 0 .…”
Section: Introductionmentioning
confidence: 99%
“…4b '' ε is positive and decrease in amplitude with the angular frequency. In equation (14), the numerator increase linearly with d Γ instead the denominator increases quadratically with d Γ Based on this observation we conclude that the increase on ε [18,19].…”
Section: Analysis and Resultsmentioning
confidence: 60%
“…Another challenge is the difficulty in integrating the plasmonic materials with current semiconductor fabrication processes. Novel plasmonic materials including transition metal nitrides and conductive oxides have received significant attention in recent years due to their tunable plasmonic response in this wavelength range and crystalline growth techniques . However, their plasma wavelengths are also limited to the visible through NIR wavelengths, and the epitaxial integration of these materials with current III–V‐based optoelectronic and nanophotonic devices remains to be addressed.…”
Section: Sample Parameters Of Nine Co‐deposited Eras:gaas Filmsmentioning
confidence: 99%